Asset prices and current account fluctuations in G7 economies - Marcel Fratzscher; Roland Straub (European Central Bank (ECB), 2009)
The paper analyses the effect of equity price shocks on current account positions for the G7 industrialized countries in 1974-2007. It uses a Bayesian VAR with sign restrictions for the identification of asset price shocks and to test empirically for their effect on current accounts. Such shocks are found to exert a sizeable effect, with a 10 percent equity price increase for instance in the United States relative to the rest of the world worsening the US trade balance by 0.9 percentage points after 16 quarters. However, the response of the trade balance to equity price shocks varies substantially across countries. The evidence suggests that the channels accounting for this heterogeneity function both through wealth effects on private consumption and to some extent through the real exchange rate of countries.
Keywords: E2; F32; F40; G1; 330; asset prices; Bayesian VAR; current account; financial markets; Identification; industrialized economies; Börsenkurs; Leistungsbilanz; G7-Staaten